Reflection of Podillian Dialect Features in the Manuscript Heritage of S. Rudanskyi (the Case Study of the Manuscript «Lirnykovi Dumy») (Linguostylistic Studies, 2017)
The article analyzes the linguistic peculiarities of S. Ridanskyi’s manuscript «Lirnykovi dumy» («Lyrist’s ballads»). The author argues that this cycle of poetry is written in the so-called «yaryzhka-style» and involves certain colloquial features. Podillia dialectal areal can be clearly recognized on the phonetic and morphological levels in the lyrics. The study reveals at the phonetic level: non-normative usage of the unstressed vowels (хрищених, ломати, беріг, пазюрі, діявил), the phenomenon of «ukannia» (pronouncing sound [u] instead of [o] in the words like домувина, dispalatalization of [t] -m (стоят, проживают), inserting consonants [l; n] after labial, ussage of dialectal forms of numerals (їден, штири), hard consonant р (зорами, морами), absence of doubling of consonants in neuter nouns of second declension; on the morphological level: usage of adjective-adverbial suffix -ішч- (найяснищій, найсыльнищій), usage of participial suffix -ан- (згубляний), in certain cases the ending -ою is used instead of -ею (земльою); usage of flexion -ів instead of zero flexion  in the forms of genitive case of plural nouns, female gender of the first declension (жабів, черепахів), genitive case-form of masculine nouns, ending in -a, singular form of the second declension (ліса, світа, віка), in the dative and prepositional cases of adjectives and impersonal pronouns of the female gender singular are characterized by truncated forms of endings (omission of final -й, for instance, на церкви святи, у кажди церкви), usage of froms тримав-ись, підпирав-ись, etc.
Keywords: Podillian dialects; phonetic features; S.Rudanskyi; «Lirnykovi dumy» («Lyrist’s Ballads»)